Spontaneous vesicle formation in a deep eutectic solvent. Issue 6 (24th December 2015) - Bryant, Saffron J.; Atkin, Rob; Warr, Gregory G.
Abstract : Solvent penetration experiments and small-angle X-ray scattering reveal that phospholipids dissolved in a deep eutectic solvent (DES) spontaneously self-assemble into vesicles above the lipid chain melting temperature. Abstract : Solvent penetration experiments and small-angle X-ray scattering reveal that phospholipids dissolved in a deep eutectic solvent (DES) spontaneously self-assemble into vesicles above the lipid chain melting temperature. This means DESs are one of the few nonaqueous solvents that mediate amphiphile self-assembly, joining a select set of H-bonding molecular solvents and ionic liquids.